2008
DOI: 10.1021/jp711302r
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Heterogeneous Reaction of Carbonyl Sulfide on Magnesium Oxide

Abstract: The experimental determination of rate constants for atmospheric reactions and how these rate constants vary with temperature remain a crucially important part of atmosphere science. In this study, the temperature dependence of the heterogeneous reaction of carbonyl sulfide (COS) on magnesium oxide (MgO) has been investigated using a Knudsen cell reactor and a temperature-programmed reaction apparatus. We found that the adsorption and the heterogeneous reaction are sensitive to temperature. The initial uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…Destruction of OCS can also occur in the solid phase and was observed on pure mineral oxides with high basicity (Liu et al, 2008(Liu et al, , 2009(Liu et al, , 2010a. However, such catalytic reaction should be significant only in very dry soils (with only a few molecular layers of water) and in the absence of other competitive adsorbents such as CO 2 (Liu et al, 2008(Liu et al, , 2010b and is therefore neglected in our model.…”
Section: Consumption and Production Ratesmentioning
confidence: 96%
See 2 more Smart Citations
“…Destruction of OCS can also occur in the solid phase and was observed on pure mineral oxides with high basicity (Liu et al, 2008(Liu et al, , 2009(Liu et al, , 2010a. However, such catalytic reaction should be significant only in very dry soils (with only a few molecular layers of water) and in the absence of other competitive adsorbents such as CO 2 (Liu et al, 2008(Liu et al, , 2010b and is therefore neglected in our model.…”
Section: Consumption and Production Ratesmentioning
confidence: 96%
“…However these relationships obtained for organic vapours are unlikely to be applicable for OCS because the adsorption mechanisms may be completely different. Liu and colleagues have estimated OCS adsorption capacities of several mineral oxides and found that quartz (SiO 2 ) and anatase (TiO 2 ) did not adsorb OCS but other oxides with higher basicity adsorbed, reversibly or not, rather large quantities of OCS (Liu et al, 2008(Liu et al, , 2009(Liu et al, , 2010a. They also recognised that these estimates of the adsorption capacity of the minerals were an upper limit owing to the competitive adsorption of other gases such as CO 2 , H 2 O and Burnell et al (1988) This study Sun et al (2015) (d) NO x that occur in the real Earth's atmosphere (Liu et al, 2009(Liu et al, , 2010a and the somewhat lower OCS partial pressure in ambient air compared to that used in their experimental setup.…”
Section: Partitioning Of Ocs In the Different Soil Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we have measured the linear range for the observed uptake coefficient of OCS on α-Al 2 O 3 to be 0-70 mg (Liu et al, 2008b), and to be 0-100 mg on MgO (Liu et al, 2008a). In this study, we kept the sample mass to be 70.0 mg for α-Al 2 O 3 and 90.0 mg for MgO to ensure OCS molecules accessing all of the layers of particle samples within the time scale of the KCMS measurement, and BET area of sample was used to calculate γ t .…”
Section: Kcms Experimentsmentioning
confidence: 99%
“…Nonetheless, information on the kinetics of the heterogeneous reaction of OCS on mineral oxides is limited. We recently reported uptake coefficients of OCS on MgO (Liu et al, 2008a), α-Al 2 O 3 and γ -Al 2 O 3 (Liu et al, 2008b). All of these studies were performed under dry conditions.…”
Section: Introductionmentioning
confidence: 99%